Programmatic outcomes and impact of rapid public sector antiretroviral therapy expansion in adults prior to introduction of the WHO treat‐all approach in rural Eswatini. Issue 6 (1st April 2019) - Kerschberger, Bernhard; Schomaker, Michael; Ciglenecki, Iza; Pasipamire, Lorraine; Mabhena, Edwin; Telnov, Alex; Rusch, Barbara; Lukhele, Nomthandazo; Teck, Roger; Boulle, Andrew
Abstract: Objectives: To assess long‐term antiretroviral therapy (ART) outcomes during rapid HIV programme expansion in the public sector of Eswatini (formerly Swaziland). Methods: This is a retrospectively established cohort of HIV‐positive adults (≥16 years) who started first‐line ART in 25 health facilities in Shiselweni (Eswatini) between 01/2006 and 12/2014. Temporal trends in ART attrition, treatment expansion and ART coverage were described over 9 years. We used flexible parametric survival models to assess the relationship between time to ART attrition and covariates. Results: Of 24 772 ART initiations, 6% ( n = 1488) occurred in 2006, vs . 13% ( n = 3192) in 2014. Between these years, median CD4 cell count at ART initiation increased (113–265 cells/mm 3 ). The active treatment cohort expanded 8.4‐fold, ART coverage increased 8.0‐fold (7.1% in 2006 vs . 56.8% in 2014) and 12‐month crude ART retention improved from 71% to 86%. Compared with the pre‐decentralisation period (2006–2007), attrition decreased by 5% (adjusted hazard ratio [aHR] 0.95, 95% confidence interval 0.88–1.02) during HIV‐TB service decentralisation (2008–2010), by 17% (aHR 0.83, 0.75–0.92) during service consolidation (2011–2012), and by 20% (aHR 0.80, 0.71–0.90) during further treatment expansion (2013–2014). The risk of attrition was higher for young age, male sex, pathological baseline haemoglobin and biochemistry results, more toxic drug regimens, WHO III/IV staging and low CD4 cell count; access to a telephone was protective. Conclusions: Programmatic outcomes improved during large expansion of the treatment cohort and increased ART coverage. Changes in ART programming may have contributed to better outcomes. Abstract : Objectifs: Evaluer les résultats du traitement antirétroviral (ART) à long terme durant l'expansion rapide du programme de lutte contre le VIH dans le secteur public d'Eswatini (anciennement Swaziland). Méthodes: Il s'agit d'une cohorte établie de manière rétrospective d'adultes VIH positifs (≥ 16 ans) qui ont commencé un ART de première ligne dans 25 établissements de santé à Shiselweni (Eswatini) entre janvier 2006 et décembre 2014. Les tendances temporelles de l'attrition dans l'ART, de l'extension de la couverture ART ont été décrites sur 9 ans. Nous avons utilisé des modèles de survie paramétriques flexibles pour évaluer la relation entre le temps écoulé avant l'attrition dans l'ART et les covariables. Résultats: Sur 24.772 initiations à l'ART, 6% (n = 1.488) ont eu lieu en 2006 contre 13% (n = 3.192) en 2014. Entre ces années, le nombre médian de cellules CD4 au début du traitement ART a augmenté (113 à 265 cellules/mm 3 ). La cohorte de traitement actif a été multipliée par 8, 4, la couverture ART par 8, 0 (7, 1% en 2006 contre 56, 8% en 2014) et la rétention brute sous ART est passée de 71% à 86%. Par rapport à la période antérieure à la décentralisation (2006‐2007), l'attrition a diminué de 5% (rapport de risque ajusté [aHR]: 0, 95, intervalle de confiance à 95%: 0, 88 à 1, 02) au cours de la décentralisation des services VIH‐TB (2008‐2010), de 17% (HR: 0, 83; 0, 75‐0, 92) lors de la consolidation du service (2011‐2012) et de 20% (HR: 0, 80; 0, 71‐0, 90) lors de la poursuite de l'extension du traitement (2013‐2014). Le risque d'attrition était plus élevé pour le jeune âge, le sexe masculin, les résultats pathologiques de l'hémoglobine initiale et biochimiques, des schémas thérapeutiques plus toxiques, un stade III/IV de l'OMS et une faible numération des cellules CD4; l'accès au téléphone était protecteur. Conclusions: Les résultats programmatiques se sont améliorés au cours de l'expansion importante de la cohorte de traitement et de l'augmentation de la couverture ART. Les changements apportés au programme ART peuvent avoir contribué à de meilleurs résultats.